BODY IMAGE DISSATISFACTION AMONG GYM-GOERS IN BRAZIL - ROSSI,LUCIANA (2018)
ABSTRACT Introduction: During decades of epidemiological investigation, a consensus was reached regarding physical activity and its association with benefits for the health of the population, including a reduced risk for coronary diseases, hypertension, obesity, osteoporosis and depression. Such associations led to the promotion of an active life style to be included in guidelines and governmental programs and absorbed by the fitness and supplement industries, often displaying different interests although there is growing evidence of an increase in body dissatisfaction. Objective: To evaluate body dissatisfaction among gym-goers and its relationship with age, sex, participation in gym activities and nutritional status. Methods: Participants were 227 users of 3 fitness academies with an average age of 31.4 (12.3) years; 51.5% of the participants were men. Collected data were related to anthropometry and fitness activity participation, and a body image scale was applied. Results: Body image dissatisfaction was found in 67.4% of the sample, of which 64.8% expressed a desire to be slimmer. Such dissatisfaction was also present in those of normal weight, of whom 11.5% were male and 9.2% female. For women of average weight, the odds of dissatisfaction were estimated to be 0.20-fold greater than for men (p<10-6). Discussion: Fitness academies in Brazil and several other parts of the world, with an approach based on the fitness model that emphasizes the cult of the body beautiful, are likely to attract a male audience more inclined to experience body dissatisfaction. Constant monitoring of nutritional care is recommended for these individuals, in order to prevent exaggerated body dissatisfaction patterns Conclusions: Body image dissatisfaction was greater among female athletes who wished to achieve a slimmer look. Due to the large number of eutrophic gym-goers with body image dissatisfaction, campaigns for adequate body weight maintenance are recommended. These would take the emphasis off the adoption of body types with low fat percentages and risky behaviors like diets and food restriction, which trigger eating disorders. Level of Evidence I; Diagnostic studies - Investigating a diagnostic test.